The Role of Customer Loyalty in Mediating Relationship Marketing and Brand Image Effects on Customer Retention in Non-Formal Education - Tsardosslapito, Tsardosslapito; Nugroho, Arif; Akbarona, Danang Aziz (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to examine the effect of Relationship Marketing (RM) and Brand Image (BI) on Customer Loyalty (CL) and Customer Retention (CR) in English language courses. Specifically, this study analyzes the direct influence of RM and BI on CL and CR, as well as the mediating role of CL in the relationship between antecedent variables and CR. The research approach used is quantitative, with data obtained through a survey of 421 parents of active students using an online questionnaire at twenty learning centers of LKP Build Better Communication e. Data analysis was performed using the Partial Least Squares-based Structural Equation Modeling (SEM-PLS) method. The results showed that Brand Image had a significant positive effect on Customer Loyalty (β = 0.533; p < 0.000) and Customer Retention (β = 0.102; p = 0.037). Relationship Marketing also has a significant effect on Customer Loyalty (β = 0.314; p < 0.000) and Customer Retention (β = 0.128; p = 0.006). In addition, Customer Loyalty has a strong and significant effect on Customer Retention (β = 0.727; p < 0.000). The mediation analysis results show that Customer Loyalty significantly mediates the relationship between Brand Image and Customer Retention (β = 0.402; p < 0.000), as well as between Relationship Marketing and Customer Retention (β = 0.228; p < 0.000). Overall, Brand Image and Relationship Marketing play an important role in increasing Customer Loyalty and maintaining Customer Retention, with Customer Loyalty as the main explanatory mechanism. These findings indicate that training institutions need to prioritize relationship-based strategies and brand image strengthening to increase long-term customer retention.